2019
DOI: 10.1161/hypertensionaha.119.13672
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Duration and Degree of Hypertension and Body Weight on New-Onset Atrial Fibrillation

Abstract: Hypertension and obesity are known risk factors for atrial fibrillation (AF). However, it is unclear whether uncontrolled, long-standing hypertension has a particularly profound effect on AF. Because they have a similar underlying pathophysiology, hypertension and obesity could act synergistically in the context of AF. We evaluated how various stages of hypertension and body weight status affect new-onset AF. We analyzed a total of 9 797 418 participants who underwent a national health checkup. Hypertension wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 31 publications
5
57
0
1
Order By: Relevance
“…Obesity is associated with a 50% increase in AF risk and has also shown as an independent risk for AF [19,36]. Synergistically with hypertension, body weight status has been shown to be associated with new-onset AF [37].…”
Section: Mets Is a Major Risk For Atrial Cardiomyopathy And Afmentioning
confidence: 99%
“…Obesity is associated with a 50% increase in AF risk and has also shown as an independent risk for AF [19,36]. Synergistically with hypertension, body weight status has been shown to be associated with new-onset AF [37].…”
Section: Mets Is a Major Risk For Atrial Cardiomyopathy And Afmentioning
confidence: 99%
“…Overweight and obesity are known risk factors for new-onset AF (24). Yun Gi Kim et al (25) found that the degree and duration of hypertension, as well as the presence of hypertension, were important factors for new-onset AF. Body weight status was signi cantly associated with new-onset AF and acted synergistically with hypertension.…”
Section: Body Weight and New-onset Afmentioning
confidence: 99%
“…AF often leads to complications such as stroke, systemic thromboembolism and chronic heart failure [ 2 ]. In connection with the high prevalence and social importance of AF, continuing research into the causes, mechanisms of development and progression of this arrhythmia, the prevalence of AF, obesity and arterial hypertension have been steadily increasing in recent decades [ 3 ]. Epidemiological data largely explain the high prevalence of AF in young and middle-aged people without traditional causes of this arrhythmia (coronary artery disease, chronic heart failure, heart valve diseases) with abdominal obesity and hypertension, which are independent risk factors for AF [ 4 ].…”
Section: Introductionmentioning
confidence: 99%